Khaya senegalensis inhibits piroxicam mediated gastro-toxicity in wistar rats - Fatima Nnawodu Ishaq; Abdulkadir Umar Zezi; Temidayo Olutoyin Olurishe (Mashhad University of Medical Sciences, 2014)
Objective:The purpose of this study was to investigate the effects of piroxicam co-administration with ethanolic stem-bark extract of Khaya senegalensis on biomarkers of oxidative stress and gastro-toxicity in Wistar rats. Materials and Methods: Thirty healthy male and female Albino Wistar rats (190-220 g) were grouped into six (n = 5) with designated treatments including: Normal saline, piroxicam (20 mg/kg), extract (200 and 400 mg/kg) alone and both doses of the extract co-administered with piroxicam. The drugs were administered orally to all the rats for fourteen consecutive days and on the fifteenth day, they were euthanized with chloroform inhalation. Blood samples and the stomachs were isolated for evaluation of the oxidative stress biomarkers and gastro integrity, respectively. Results: The results of the study revealed that the levels of oxidative stress markers didn't differ significantly between the groups receiving the extract alone, the extract in combination or piroxicam alone. Gross and histological observations of the stomach showed gastric mucosal changes and mild atrophic lesions in the piroxicam group only. Conclusion: This study illustrates the interaction of Khaya senegalensis and piroxicam results in the gastro-protective beneficial effects. The extract's outcome on various prostaglandin levels and synthesis is being considered towards possible elucidation regarding the exact mechanism of cytoprotection.